Penggunaan Ultrasonik untuk Transesterifikasi Minyak Goreng Bekas - Supardan, Muhammad Dani (Jurnal Rekayasa Kimia & Lingkungan, 2011)
In this work, the ultrasound-assisted transesterification of used frying oil (UFO) was studied. A two-step pretreatment of degumming and esterification was conducted to prepare UFO as raw material for transesterification. The esterification and transesterification was performed by using ethanol as solvent in the presence of ultrasonic irradiations operating at frequency of 40 kHz. The esterification was carried out with oil to ethanol ratio of 1:10, temperature of 60oC and reaction time of 4 hours in the presence of 1 wt .% H2SO4 as an acid catalyst. Meanwhile, the transesterification reaction was carried out with oil to ethanol molar ratio of 1:8, 1:10, 1:12, 1:15; KOH catalyst concentration of 0.5, 0.75, 1, 1.25 and 1.5 wt.%; and reaction temperature of 40, 50 and 60oC. The highest biodiesel yield of 65% obtained at ultrasound-assisted transesterification condition of oil to ethanol molar ratio of 1:12, reaction temperature of 50oC and KOH concentration of 1 wt.%. The results of analysis of some parameters of the product showed biodiesel has fulfilled the specifications according to the Indonesian National Standard (SNI) 04-7182-2006 number.Keywords: Biodiesel, Esterification, Used frying oil, Transesterification, Ultrasonic